Rod crystal form mechanoluminescent powder, mechanoluminescent elastic composite material and preparation method thereof
By using Elosite nanotubes as Al/Si matrix, rod crystalline force electroluminescent powders were prepared and combined in organic polymers, the problem of low performance of existing Ca0.6Sr0.4Al2Si2O8:Eu2+ force electroluminescent materials was solved, and significantly improved photo afterglow and force electroluminescent properties were achieved.
Patent Information
- Application Number
- CN202411479431.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing Ca0.6Sr0.4Al2Si2O8:Eu2+ force electroluminescent materials have low photo-induced afterglow and force electroluminescent properties, which are difficult to meet practical application requirements.
Elosite nanotubes are used as the Al/Si matrix, and rod crystalline force electroluminescent powder is prepared by mixing with CaCO3, SrCO3 and Eu2O3 and a multi-step preparation process (pre-fired, grinding, sintering, etc.), and the rod crystalline force electroluminescent powder is prepared and composited in an organic polymer elastic carrier to form a force electroluminescent elastic composite material.
It significantly improves the photo afterglow and electroluminescent properties of the electroluminescent powder, provides a new idea for photo afterglow improvement of aluminosilicate luminescent materials, and expands the scope of materials for electroluminescent applications.
Smart Images

Figure CN119776002A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mechanoluminescent materials, and in particular to a rod-shaped mechanoluminescent powder and a mechanoluminescent elastic composite material and a preparation method thereof. Background Art
[0002] As a special photoluminescent energy-saving material, long afterglow luminescence (LPL) materials are widely used in display, biomedicine, energy and environmental engineering. Silicates are generally considered to be the main candidates for matrix materials in LPL materials, and aluminum matrix, as the matrix material of LPL, has excellent chemical stability and high excitation efficiency. Therefore, researchers combined the advantages of silicate and aluminate matrices, and finally further optimized the overall performance of the LPL system by integrating the favorable properties of the two materials. For example, SrAl2Si2O8:Eu 2+ ,Dy 3+ 、CaAl2Si2O8:Eu 2+ wait.
[0003] Chemical substitution is an important concept in designing new materials and improving the functional properties of known compounds. Mechanoluminescence (ML) is a luminescent behavior of materials under mechanical stimulation. It can directly convert mechanical energy into light energy, bridging the gap between microstructure and macroscopic material properties with photons as the medium. In the field of mechanoluminescence, partial substitution of cations can change the crystal structure and adjust the luminescence properties in a predictable way. 2+ Partial replacement of Ca 2+ , which increases the disorder of atoms in the lattice and can improve the CaAl2Si2O8:Eu 2+ Phosphor mechanoluminescence intensity, Sr 2+ The local change of crystal symmetry caused by substitution is the key to luminescence enhancement. However, the photoluminescence afterglow and mechanoluminescence performance of mechanoluminescent materials obtained by this doping method are still low. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a rod-shaped mechanoluminescent powder and a mechanoluminescent elastic composite material and a preparation method thereof. The present invention uses halloysite nanotubes as an Al / Si matrix, and the photoluminescent afterglow and mechanoluminescence properties of the obtained mechanoluminescent powder are significantly improved.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a rod-shaped crystal-type force-induced luminescent powder, comprising the following steps:
[0007] According to the chemical formula Ca 0.6 Sr 0.4 Al2Si2O8:xEu2+ The chemical formula of CaCO3, SrCO3, halloysite nanotubes and Eu2O3 is shown in the stoichiometric ratio, and the mixture is obtained. 0.6 Sr 0.4 Al2Si2O8:xEu 2+ wherein 0.005≤x≤0.025, the halloysite nanotubes are calculated as Al2O3 and SiO2;
[0008] The mixed material is sequentially subjected to pre-sintering, first grinding, sintering and second grinding to obtain the rod-shaped luminescent powder; the sintering is performed in a mixed atmosphere of hydrogen and inert gas.
[0009] Preferably, before the mixing, the halloysite nanotubes are pretreated, and the pretreatment method is: the halloysite nanotubes are mixed with ethanol, subjected to microwave treatment, and then dried.
[0010] Preferably, the mixing method is: wet-grinding the CaCO3, SrCO3, halloysite nanotubes and Eu2O3 and then drying them.
[0011] Preferably, the pre-burning temperature is 600-900° C. and the time is 3-5 hours.
[0012] Preferably, the inert gas is nitrogen, and the volume ratio of nitrogen to hydrogen in the mixed atmosphere is 9:1; the sintering temperature is 1000-1400° C., and the sintering time is 3-5 hours.
[0013] The present invention provides a rod-shaped luminescent powder prepared by the preparation method described in the above technical solution.
[0014] The present invention also provides a mechanoluminescent elastic composite material, comprising an organic polymer elastic carrier and mechanoluminescent powder compounded in the organic polymer elastic carrier, wherein the mechanoluminescent powder is the rod-crystal mechanoluminescent powder described in the above technical solution.
[0015] Preferably, the organic polymer elastic carrier includes polydimethylsiloxane, polyurethane or silicone.
[0016] Preferably, the mass ratio of the mechanoluminescent powder to the organic polymer elastic carrier is (0.5-2):1.
[0017] The present invention provides a method for preparing the mechanoluminescent elastic composite material described in the above technical solution, comprising the following steps:
[0018] The prepolymer of the organic polymer elastic carrier, the curing agent and the mechanoluminescent powder are mixed, and heated to be cured to obtain the mechanoluminescent elastic composite material.
[0019] The present invention provides a method for preparing a rod-shaped luminescent powder, comprising the following steps: 0.6 Sr 0.4 Al2Si2O8:xEu 2+ (0.005≤x≤0.025) shown in the stoichiometric ratio, weigh CaCO3, SrCO3, halloysite nanotubes (HNTs) and Eu2O3 to mix and obtain a mixture; the halloysite nanotubes are calculated as Al2O3 and SiO2; the mixture is pre-sintered, first ground, sintered and second ground in sequence to obtain the rod-shaped mechanoluminescent powder. The present invention uses HNTs with nanotube structure as Al / Si matrix to prepare Ca 0.6 Sr 0.4 Al2Si2O8:Eu 2+ The mechanoluminescent powder improves the photoluminescent afterglow and mechanoluminescent performance of the mechanoluminescent powder by utilizing the confinement effect of the HNTs structure and the increase of oxygen vacancies in the material preparation process. 0.6 Sr 0.4 Al2Si2O8:Eu 2+ The problem of low brightness of mechanoluminescence materials also provides a new idea for improving the photoafterglow of aluminosilicate luminescent materials. On the other hand, applying HNTs to the field of mechanoluminescence has greatly expanded the material scope of mechanoluminescence applications.
[0020] The present invention provides a mechanoluminescent elastic composite material, comprising an organic polymer elastic carrier and a mechanoluminescent powder compounded in the organic polymer elastic carrier, wherein the mechanoluminescent powder is the rod-crystal mechanoluminescent powder described in the above technical solution. The mechanoluminescent powder of the present invention has excellent photoluminescence and mechanoluminescence performance in the organic polymer elastic carrier, and the mechanoluminescence intensity can be used to realize visual sensing of stress magnitude. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The Ca prepared in Example 1 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / PDMS (H) and Ca prepared in Comparative Example 1 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / Mechanoluminescence spectrum of PDMS under the same conditions;
[0022] Figure 2 The Ca prepared in Comparative Example 1 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / PDMS (a) and Ca prepared in Example 1 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / PDMS(H)(b) photoafterglow spectrum under the same conditions;
[0023] Figure 3 X-ray diffraction spectra of CSASE (H) prepared in Example 1 and CSASE mechanoluminescent powder prepared in Comparative Example 1;
[0024] Figure 4 The SEM image (a) of the CSASE mechanoluminescent powder prepared in Comparative Example 1 and the SEM image (b) of the CSASE (H) mechanoluminescent powder prepared in Example 1;
[0025] Figure 5 The mechanoluminescent elastic composite material Ca prepared in Examples 1 to 5 0.6 Sr 0.4 Al2Si2O8:xEu 2+ / Mechanoluminescence spectra of PDMS(H) (x=0.005, 0.010, 0.015, 0.020, 0.025) under the same conditions;
[0026] Figure 6 The O1s XPS fine spectra of CSASE (H) prepared in Example 1 and CSASE mechanoluminescent powder prepared in Comparative Example 1 are shown. DETAILED DESCRIPTION
[0027] The present invention provides a method for preparing a rod-shaped crystal-type force-induced luminescent powder, comprising the following steps:
[0028] According to the chemical formula Ca 0.6 Sr 0.4 Al2Si2O8:xEu 2+ The chemical formula of CaCO3, SrCO3, halloysite nanotubes and Eu2O3 is shown in the stoichiometric ratio, and the mixture is obtained. 0.6 Sr 0.4 Al2Si2O8:xEu 2+ wherein 0.005≤x≤0.025, the halloysite nanotubes are calculated as Al2O3 and SiO2;
[0029] The mixed material is sequentially subjected to pre-sintering, first grinding, sintering and second grinding to obtain the rod-shaped luminescent powder; the sintering is performed in a mixed atmosphere of hydrogen and inert gas.
[0030] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.
[0031] The present invention is based on the chemical formula Ca 0.6 Sr 0.4 Al2Si2O8:xEu 2+ According to the stoichiometric ratio shown in FIG. 1 , CaCO3, SrCO3, halloysite nanotubes and Eu2O3 are weighed and mixed to obtain a mixture. In the present invention, the chemical formula Ca 0.6 Sr 0.4 Al2Si2O8:xEu 2+ 0.005≤x≤0.025 (x is Eu 2+ The doping molar ratio or doping molar percentage is 1 mol of Ca 0.6 Sr 0.4 Al2Si2O8:xEu 2+ Eu 2+ The molar amount of x is x), wherein x can be 0.005, 0.010, 0.015, 0.020, 0.025, preferably 0.015. In the present invention, the halloysite nanotubes are calculated in terms of Al2O3 and SiO2. In the present invention, the chemical formula of Ca 0.6 Sr 0.4 Al2Si2O8:xEu 2+ The stoichiometric ratio shown is the molar ratio of Ca:Sr:Al:Si:Eu 2+ =0.6:0.4:2:2:x. In the embodiment of the present invention, the purity of the CaCO3 is 99.9%, the purity of the SrCO3 and Eu2O3 are 99.99% respectively, and the purity of the halloysite nanotube is preferably >99%.
[0032] Halloysite nanotubes (Al2O3·2SiO2·4H2O, HNTs) are 1:1 layered aluminum silicate minerals, consisting of silicon-oxygen tetrahedron layers and aluminum-oxygen octahedron layers. The oxygen atoms shared by each silicon-oxygen tetrahedron and aluminum-oxygen octahedron are apical oxygen atoms, and the remaining three oxygen atoms are basal oxygen atoms. Adjacent silicon-oxygen tetrahedrons share basal oxygen atoms and are connected to each other at specific angles to form silicon-oxygen tetrahedron layers. Each aluminum-oxygen octahedron is composed of four hydroxyl groups, one aluminum atom, and two apical oxygen atoms of silicon-oxygen tetrahedrons, wherein the hydroxyl groups are shared with adjacent aluminum-oxygen octahedrons, and they are connected to each other to form a unique tubular structure. Its special Al2O3 / SiO2 composition and structural morphology provide a basis for the preparation of CaO2 with different morphologies by the present invention. 0.6 Sr 0.4 Al2Si2O8:Eu 2+Provides a possibility. Carriers trapped in lattice defects (traps) play a vital role in the generation of mechanoluminescent materials (ML). The trapped carriers (electrons and / or holes) are released by stress energy and then recombined in the emission center to generate ML. Therefore, the formation of lattice defects that can capture more carriers under ultraviolet excitation is an effective means to enhance ML emission. Compared with the raw materials SiO2 and Al2O3, the present invention uses HNTs with a nanotubular structure as the Al / Si matrix. The HNTs rich in oxygen atoms will form more oxygen vacancies during the calcination process when hydroxyl groups are removed and water molecules evaporate, which is Ca 0.6 Sr 0.4 Al2Si2O8:Eu 2+ The enhancement of mechanoluminescence provides a basis.
[0033] Before mixing, the present invention preferably pre-treats the halloysite nanotubes, and the pre-treatment method is preferably: mixing the halloysite nanotubes with ethanol, subjecting them to microwave treatment, and then drying. In the present invention, the dosage ratio of the halloysite nanotubes to ethanol is preferably 5g:50mL. In the present invention, the microwave treatment time is preferably 30min, and the drying is preferably dried at 100°C. The present invention mixes the halloysite nanotubes with ethanol and subjecting them to microwave treatment, so that the halloysite nanotubes are dispersed, so that subsequent reactions can be fully carried out. Since HNTs will lose adsorbed water during the drying process (two molecules of water in HNTs belong to adsorbed water, which will be lost during the drying process, which is a characteristic of HNTs), the weighed weight of the HNTs is calculated according to the molecular formula Al2O3·2SiO2·2H2O to ensure the accuracy of the weighing.
[0034] In the present invention, the mixing method is preferably to wet-grind the CaCO3, SrCO3, halloysite nanotubes and Eu2O3 and then dry. In the present invention, the grinding medium added in the wet grinding is preferably ethanol; the specific operation of the mixing is preferably: mixing the CaCO3, SrCO3, halloysite nanotubes and Eu2O3 in an agate mortar, adding ethanol and grinding them fully. The present invention has no special requirements for the drying conditions.
[0035] After obtaining the mixture, the present invention sequentially pre-fires, first grinds, sinters and second grinds the mixture to obtain the rod-shaped luminescent powder. In the present invention, the pre-fire temperature is preferably 600-900°C, which can be 600, 700, 800, 900°C, and the time is preferably 3-5h, which can be 3, 4, 5h. The present invention preferably transfers the mixture to an alumina crucible and pre-fires in a box-type resistance furnace. In the present invention, the pre-fire is to ensure uniform mixing of materials and preliminary solid-phase reaction, remove crystal water in the material and allow some substances (such as CaCO3) to decompose in advance (CaO and CO2) to form precursors, so as to facilitate better subsequent reactions. After the pre-fire, the mixture is cooled and the pre-fired sample is first ground into powder.
[0036] In the present invention, the sintering is carried out in a mixed atmosphere of hydrogen and inert gas, and the inert gas is preferably nitrogen. The volume ratio of nitrogen and hydrogen in the mixed atmosphere is preferably 9:1. In the present invention, the sintering temperature is preferably 1000-1400°C, and can be 1000, 1100, 1200, 1300, 1400°C. The time is preferably 3-5h, and can be 3, 4, 5h. The heating rate from room temperature to the sintering temperature is preferably 4.5-5.5°C / min, and can be 4.5, 5, 5.5°C / min. In the present invention, the sintering is preferably carried out in a tubular furnace. During the sintering process, the material gradually crystallizes to form Ca with a relatively complete crystal structure. 0.6 Sr 0.4 Al2Si2O8 phase. This process involves the rearrangement and combination of the elements in the raw materials to form a stable crystal structure. After the sintering, the sintered sample is cooled to room temperature and the obtained sintered sample is first ground into powder to obtain the rod-shaped mechanoluminescent powder. In the embodiment of the present invention, the mechanoluminescent powder is represented as CSASE (H) luminescent powder.
[0037] The invention adopts a high-temperature solid phase method to prepare the mechanoluminescent powder, which is simple to operate and easy to industrialize and apply.
[0038] The present invention provides a rod-shaped mechanoluminescent powder prepared by the preparation method described in the above technical solution. In the present invention, the mechanoluminescent powder is in the shape of a rod-shaped crystal, and the formation of the rod-shaped crystal is caused by the confinement effect of HNTs, which introduces internal stress, thereby improving the mechanoluminescence performance.
[0039] The present invention also provides a mechanoluminescent elastic composite material, comprising an organic polymer elastic carrier and mechanoluminescent powder compounded in the organic polymer elastic carrier, wherein the mechanoluminescent powder is the rod-crystal mechanoluminescent powder described in the above technical solution.
[0040] In the present invention, the organic polymer elastic carrier preferably includes polydimethylsiloxane (PDMS), polyurethane (PU, such as thermoplastic polyurethane elastomer) or silicone, more preferably PDMS. The present invention has no special requirements for the PDMS, PU or silicone, and the corresponding materials well known to those skilled in the art can be used. In the present invention, the mass ratio of the mechanoluminescent powder to the organic polymer elastic carrier is preferably (0.5-2):1, more preferably 0.5:1, 1:1.5 or 2:1.
[0041] The mechanoluminescent elastic composite material provided by the present invention has high luminous efficiency, high brightness and light-induced afterglow, can meet practical application requirements to a certain extent, and has good application prospects.
[0042] The present invention provides a method for preparing the mechanoluminescent elastic composite material described in the above technical solution, comprising the following steps:
[0043] The prepolymer of the organic polymer elastic carrier, the curing agent and the mechanoluminescent powder are mixed, and heated to be cured to obtain the mechanoluminescent elastic composite material.
[0044] In the present invention, the prepolymer and curing agent of the organic polymer elastic carrier are preferably prepolymers and curing agents corresponding to elastomers such as polydimethylsiloxane, polyurethane, and silicone. The present invention has no special requirements on the types and ratios of the prepolymers and curing agents, and the corresponding prepolymers and curing agents and ratios well known to those skilled in the art can be used; in an embodiment of the present invention, the prepolymer is a PDMS prepolymer, and the mass ratio of the PDMS prepolymer to the curing agent is 1:0.1. In the present invention, the total mass ratio of the mechanoluminescent powder to the prepolymer and curing agent of the organic polymer elastic carrier is preferably (0.5-2):1, more preferably 0.5:1, 1:1.5 or 2:1.
[0045] In the present invention, the method for mixing the prepolymer of the organic polymer elastic carrier, the curing agent and the mechanoluminescent powder is preferably: uniformly mix the prepolymer of the organic polymer elastic carrier and the curing agent, then add the mechanoluminescent powder thereto, and fully mix by mechanical stirring. After the mixing, the present invention preferably transfers the obtained mixture to a mold, and then transfers the mold to a vacuum oven for vacuum degassing treatment; the temperature of the vacuum degassing treatment is preferably room temperature, the vacuum degree is preferably 10 to 20 kPa, and the time is preferably 10 to 20 minutes.
[0046] The present invention has no special requirements for the curing conditions, and the curing conditions known to those skilled in the art can be used; in the embodiment of the present invention, the curing temperature is preferably 50 to 80° C., and the curing time is preferably 20 to 60 minutes. After the curing, the mechanoluminescent elastic composite material is obtained.
[0047] In order to further illustrate the present invention, the rod-shaped mesoluminescent powder and mesoluminescent elastic composite material provided by the present invention and their preparation are described in detail below in combination with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0048] In various embodiments, the composition of the mechanoluminescent elastic composite material is represented by Ca 0.6 Sr 0.4 Al2Si2O8:xEu 2+ / PDMS, where x is the molar doping concentration of Eu ions (i.e., 1 mol of Ca 0.6 Sr 0.4 Al2Si2O8:xEu 2+ Eu 2+ The molar amount is x).
[0049] Example 1
[0050] A method for preparing a rod-shaped mechanoluminescent powder and a mechanoluminescent elastic composite material thereof, comprising the following steps:
[0051] (1) Preparation of mechanoluminescent powder:
[0052] The HNTs were placed in ethanol and microwaved for 30 min, and then dried at 100 °C for later use. 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ ) Weigh SrCO3 (99.99%), CaCO3 (99.9%), HNTs (>99%) and Eu2O3 (99.99%), mix them in an agate mortar, add ethanol and grind them thoroughly, transfer them to an alumina crucible after drying, and pre-sinter the raw materials at 700℃ for 4h in a box-type resistance furnace. After cooling, grind the pre-sintered samples into powder. Then, place the alumina crucible containing the pre-sintered samples in a tube furnace (GSL-1600X) in a nitrogen-hydrogen (volume ratio 9:1) mixed atmosphere for 4h, with a heating rate of 5℃ / min and a sintering temperature of 1200℃. After the tube furnace is cooled to room temperature, take out the samples and grind them into powder again to obtain a mesoluminescent powder, which is recorded as CSASE(H).
[0053] (2) Preparation of mechanoluminescent elastic composite materials:
[0054] The prepolymer polydimethylsiloxane (PDMS) and the curing agent were uniformly mixed at a mass ratio of 1:0.1, and then the mechanoluminescent powder (CSASE (H)) prepared in step (1) was mixed with the above mixture at a mass ratio of 1:1.5, and after being fully mixed by mechanical stirring, the mixture was transferred to the mold. At room temperature, the mold was moved to a vacuum oven with a vacuum degree of 20 kPa for degassing for 10 minutes to eliminate bubbles; then it was cured at 70°C for 30 minutes to obtain a mechanoluminescent elastic composite material, which was recorded as Ca 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / PDMS(H).
[0055] Comparative Example 1
[0056] The HNTs in step (1) of Example 1 were replaced by SiO2 (99.9%) and Al2O3 (99.9%), and the rest was the same as Example 1 to obtain a mechanoluminescent powder (denoted as CSASE) and a mechanoluminescent elastic composite material (denoted as Ca 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / PDMS).
[0057] Figure 1 The mechanoluminescent elastic composite material Ca prepared in Example 1 is given. 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / PDMS (H) and the mechanoluminescent elastic composite material Ca prepared in Comparative Example 1 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ The force-induced luminescence spectrum of / PDMS under the same conditions (tensile deformation is 80%). Figure 1 It can be seen that when the tensile deformation is 80%, the mechanoluminescent elastic composite material Ca prepared in Example 1 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / PDMS(H) (curve 1) has a significantly higher mesoluminescence intensity than Ca 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / PDMS (curve 2).
[0058] Figure 2 The mechanoluminescent elastic composite material Ca prepared in Example 1 is given. 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / PDMS (H) and the mechanoluminescent elastic composite material Ca prepared in Comparative Example 1 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / PDMS photoinduced afterglow spectrum under the same conditions. Figure 2 It can be seen that after 5 min of ultraviolet (365 nm) irradiation, the mechanoluminescent elastic composite material Ca prepared in Example 1 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / PDMS(H)( Figure 2 b) The photoperiod afterglow is significantly better than that of Ca 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / PDMS( Figure 2 a).
[0059] Figure 3 The X-ray diffraction spectra of CSASE (H) prepared in Example 1 and CSASE mechanoluminescent powder prepared in Comparative Example 1 were measured on an Auriga / Shimadzu XRD-6100 X-ray diffractometer. Figure 3 It can be seen that the two have similar crystal structures.
[0060] Figure 4 The scanning electron microscope images of the mechanoluminescent powder CSASE (H) prepared in Example 1 and the mechanoluminescent powder CSASE prepared in Comparative Example 1 are shown in FIG. Figure 4 In the figure, a corresponds to CSASE, and b corresponds to CSASE(H). It can be seen that the two have different morphological characteristics. The CSASE(H) mesoluminescent powder has a rod-shaped crystal morphology.
[0061] Figure 6 The O 1s XPS fine spectra of CSASE (H) prepared in Example 1 and CSASE mechanoluminescent powder prepared in Comparative Example 1 are shown in FIG. Figure 6 Medium Ⅰ represents lattice oxygen, O Ⅱ represents an oxygen vacancy. Figure 6 It can be seen that the oxygen vacancies (O Ⅱ ) has increased significantly.
[0062] Example 2
[0063] A method for preparing a rod-shaped mechanoluminescent powder and a mechanoluminescent elastic composite material thereof, comprising the following steps:
[0064] Compared with Example 1, x is 0.005, and the rest is the same as steps (1) and (2) in Example 1. The obtained electroluminescent elastic composite material is denoted as Ca0.6 Sr 0.4 Al2Si2O8:0.005Eu 2+ / PDMS(H).
[0065] Figure 5 The Ca prepared in Example 1 is given 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ The mechanoluminescence spectrum of the / PDMS(H) mechanoluminescent elastic composite material (curve 3) and the Ca prepared in Example 2 0.6 Sr 0.4 Al2Si2O8:0.005Eu 2+ / PDMS (H) mechanoluminescence spectrum (curve 1), the characterization conditions of Example 2 are consistent with those of Example 1, Figure 5 It can be seen that the mechanoluminescent elastic composite material Ca prepared in Example 2 0.6 Sr 0.4 Al2Si2O8:0.005Eu 2+ / PDMS(H) (curve 1) has a lower luminescence intensity than curve 3.
[0066] Example 3
[0067] A method for preparing a rod-shaped mechanoluminescent powder and a mechanoluminescent elastic composite material thereof, comprising the following steps:
[0068] Compared with Example 1, x is 0.010, and the rest is the same as steps (1) and (2) in Example 1. The obtained electroluminescent elastic composite material is denoted as Ca 0.6 Sr 0.4 Al2Si2O8:0.010Eu 2+ / PDMS(H).
[0069] Figure 5 The Ca prepared in Example 3 is given. 0.6 Sr 0.4 Al2Si2O8:0.010Eu 2+ The mechanoluminescence spectrum of the / PDMS(H) mechanoluminescent elastic composite material (curve 2) is consistent with the characterization conditions of Example 1. Figure 5 It can be seen that the mechanoluminescent elastic composite material Ca prepared in Example 3 0.6 Sr 0.4 Al2Si2O8:0.010Eu 2+ / PDMS(H) (curve 2) has a lower luminescence intensity than curve 3 and a higher luminescence intensity than curve 1.
[0070] Example 4
[0071] A method for preparing a rod-shaped mechanoluminescent powder and a mechanoluminescent elastic composite material thereof, comprising the following steps:
[0072] Compared with Example 1, x is 0.020, and the rest is the same as steps (1) and (2) in Example 1. The obtained electroluminescent elastic composite material is denoted as Ca 0.6 Sr 0.4 Al2Si2O8:0.020Eu 2+ / PDMS(H).
[0073] Figure 5 The Ca prepared in Example 4 is given 0.6 Sr 0.4 Al2Si2O8:0.020Eu 2+ The mechanoluminescence spectrum of the / PDMS(H) mechanoluminescent elastic composite material (curve 4) is consistent with the characterization conditions of Example 1. Figure 5 It can be seen that the mechanoluminescent elastic composite material Ca prepared in Example 4 0.6 Sr 0.4 Al2Si2O8:0.020Eu 2+ / PDMS(H) (curve 4) has a lower luminescence intensity than curves 3 and 2, but higher than curve 1.
[0074] Example 5
[0075] A method for preparing a rod-shaped mechanoluminescent powder and a mechanoluminescent elastic composite material thereof, comprising the following steps:
[0076] Compared with Example 1, x is 0.025, and the rest is the same as steps (1) and (2) in Example 1. The obtained electroluminescent elastic composite material is denoted as Ca 0.6 Sr 0.4 Al2Si2O8:0.025Eu 2+ / PDMS(H).
[0077] Figure 5 The Ca prepared in Example 5 is given. 0.6 Sr 0.4 Al2Si2O8:0.025Eu 2+ The mechanoluminescence spectrum of the / PDMS(H) mechanoluminescent elastic composite material (curve 5) is consistent with the characterization conditions of Example 1. Figure 5 It can be seen that the mechanoluminescent elastic composite material Ca prepared in Example 5 0.6 Sr 0.4 Al2Si2O8:0.025Eu 2+ / PDMS(H) (curve 5) has a lower luminescence intensity than curves 3 and 2, but higher than curve 1.
[0078] Depend on Figure 5 It can be seen that with the increase of Eu doping concentration, the mesoluminescence intensity of the material shows a trend of first increasing and then decreasing. Figure 1 and Figure 2 It can be seen that when the doping concentration of Eu is 0.015, the material Ca 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ The photoluminescence and mechanoluminescence intensities of / PDMS(H) are better than those of Ca 0.6 Sr 0.4 Al2Si2O8:0.015Eu 2+ / PDMS.
[0079] Example 6
[0080] A method for preparing a rod-shaped mechanoluminescent powder and a mechanoluminescent elastic composite material thereof, comprising the following steps:
[0081] Compared with Example 1, x is 0.005, the polymer is silica gel, the mass ratio of prepolymer (silicone prepolymer and curing agent) to luminescent powder CSASE (H) is 1:0.5, the curing temperature is 60° C., and the curing time is 60 min.
[0082] Example 7
[0083] A method for preparing a rod-shaped mechanoluminescent powder and a mechanoluminescent elastic composite material thereof, comprising the following steps:
[0084] Compared with Example 1, x is 0.02, the polymer is polyurethane, the mass ratio of the prepolymer (polyurethane prepolymer and curing agent) and the luminescent powder CSASE (H) is 1:2, the curing temperature is 60° C., and the curing time is 50 min.
[0085] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a rod-shaped luminescent powder, characterized in that: The following steps are involved: According to the chemical formula Ca 0.6 Sr 0.4 Al2Si2O8:xEu 2+ In the stoichiometric ratio shown in FIG. 1 , CaCO3, SrCO3, halloysite nanotubes and Eu2O3 are weighed and mixed to obtain a mixture; the chemical formula Ca 0.6 Sr 0.4 Al2Si2O8:xEu 2+ wherein 0.005≤x≤0.025, the halloysite nanotubes are calculated as Al2O3 and SiO2; The mixed material is sequentially subjected to pre-sintering, first grinding, sintering and second grinding to obtain the rod-shaped luminescent powder; the sintering is performed in a mixed atmosphere of hydrogen and inert gas.
2. The preparation method according to claim 1, characterized in that: Before the mixing, the halloysite nanotubes are pretreated, and the pretreatment method is: the halloysite nanotubes are mixed with ethanol, subjected to microwave treatment, and then dried.
3. The preparation method according to claim 1, characterized in that: The mixing method is: wet-grinding the CaCO3, SrCO3, halloysite nanotubes and Eu2O3 and then drying them.
4. The preparation method according to claim 1, characterized in that: The pre-burning temperature is 600-900° C. and the pre-burning time is 3-5 hours.
5. The preparation method according to claim 1, characterized in that: The inert gas is nitrogen, and the volume ratio of nitrogen to hydrogen in the mixed atmosphere is 9:1; the sintering temperature is 1000-1400° C., and the sintering time is 3-5 hours.
6. Rod-shaped mesoluminescent powder prepared by the preparation method according to any one of claims 1 to 5.
7. A mechanoluminescent elastic composite material, characterized in that: The invention comprises an organic polymer elastic carrier and a mesoluminescent powder compounded in the organic polymer elastic carrier, wherein the mesoluminescent powder is the rod-crystal type mesoluminescent powder as claimed in claim 6.
8. The mechanoluminescent elastic composite material according to claim 7, characterized in that: The organic polymer elastic carrier includes polydimethylsiloxane, polyurethane or silicone.
9. The mechanoluminescent elastic composite material according to claim 7 or 8, characterized in that: The mass ratio of the mechanoluminescent powder to the organic polymer elastic carrier is (0.5-2):
1.
10. The method for preparing the mechanoluminescent elastic composite material according to any one of claims 7 to 9, characterized in that: The following steps are involved: The prepolymer of the organic polymer elastic carrier, the curing agent and the mechanoluminescent powder are mixed, and heated to be cured to obtain the mechanoluminescent elastic composite material.
Citation Information
Patent Citations
ZnS-based mechanoluminescence elastic composite material based on HNTs doping and preparation method of ZnS-based mechanoluminescence elastic composite material
CN117106445A
Stress-Stimulated Luminescent Material, Manufacturing Method Thereof, Composite Material Including the Stress-Stimulated Luminescent Material, and Base Material Structure of the Stress-Stimulated Luminescent Material
US20090050847A1